2021
DOI: 10.1152/jn.00314.2021
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hsp70 attenuates nitroglycerin-induced migraine-like symptoms in mice

Abstract: Although the connection between heat shock protein 70 (HSP70) and vestibular migraine is not clear, HSP70 is neuroprotective in other scenarios. This study aimed to investigate the potential of exogenous HSP70 for treating migraine-like symptoms in a mouse model of nitroglycerin (NTG) induced migraine. HSP70 levels were assessed in patients with vestibular migraine and healthy individuals by ELISA. Migraine was induced in mice by NTG and HSP70 expression was examined in the trigeminal nucleus caudalis (TNC) ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our RNA sequencing data showed that while this gene was expressed in both sexes, it was specifically upregulated only in males post tumor growth. Interestingly, hsp70 has been demonstrated to have a protective role in pain during nerve damage 111 , 112 , migraine 113 and opioid-induced hyperalgesia 114 .Therefore, upregulation of Hsp70 in males post-tumor growth might indicate that male neurons might express an endogenous feedback mechanism to suppress pain that may be lacking in females.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA sequencing data showed that while this gene was expressed in both sexes, it was specifically upregulated only in males post tumor growth. Interestingly, hsp70 has been demonstrated to have a protective role in pain during nerve damage 111 , 112 , migraine 113 and opioid-induced hyperalgesia 114 .Therefore, upregulation of Hsp70 in males post-tumor growth might indicate that male neurons might express an endogenous feedback mechanism to suppress pain that may be lacking in females.…”
Section: Discussionmentioning
confidence: 99%
“…Our RNA sequencing data showed that while this gene was expressed in both sexes, it was specifically upregulated only in males post tumor growth. Interestingly, hsp70 has been demonstrated to have a protective role in pain during nerve damage (99,100), migraine (101) and opioid-induced hyperalgesia (102).Therefore, upregulation of Hsp70 in males post-tumor growth might indicate that male neurons might express an endogenous feedback mechanism to suppress pain that may be lacking in females. In addition to the common BPs, sex-selective BPs were identified post-tumor growth.…”
Section: Discussionmentioning
confidence: 99%

Oxidative Stress and Migraine

Jiménez-Jiménez,
Alonso-Navarro,
García-Martín
et al. 2024
Mol Neurobiol